HOTAIR‐Loaded Mesenchymal Stem/Stromal Cell Extracellular Vesicles Enhance Angiogenesis and Wound Healing. Issue 5 (18th April 2021) - Born, Louis J.; Chang, Kai‐Hua; Shoureshi, Pouria; Lay, Frank; Bengali, Sameer; Hsu, Angela Ting Wei; Abadchi, Sanaz Nourmohammadi; Harmon, John W.; Jay, Steven M.
Abstract: Chronic wounds remain a substantial source of morbidity worldwide. An emergent approach that may be well‐suited to induce the complex, multicellular processes such as angiogenesis that are required for wound repair is the use of extracellular vesicles (EVs). EVs contain a wide variety of proteins and nucleic acids that enable multifactorial signaling. Here, the capability of EVs is leveraged to be engineered via producer cell modification to investigate the therapeutic potential of EVs from mesenchymal stem/stromal cells (MSCs) transfected to overexpress long non‐coding RNA HOX transcript antisense RNA (HOTAIR). HOTAIR is previously shown by the authors' group to be critical in mediating angiogenic effects of endothelial cell EVs, and MSCs are chosen as EV producer cells for this study due to their widely reported intrinsic angiogenic properties. The results indicate that MSCs overexpressing HOTAIR (HOTAIR‐MSCs) produce EVs with increased HOTAIR content that promote angiogenesis and wound healing in diabetic (db/db) mice. Further, endothelial cells exposed to HOTAIR‐MSC EVs exhibit increased HOTAIR content correlated with upregulation of the angiogenic protein vascular endothelial growth factor. Thus, this study supports EV‐mediated HOTAIR delivery as a strategy for further exploration toward healing of chronic wounds. Abstract : An emergent approach for wound repair is the use of extracellular vesicles (EVs). Here, the therapeutic potential of EVs from mesenchymal stem/stromal cells (MSCs) transfected to overexpress long non‐coding RNA HOX transcript antisense RNA (HOTAIR) is investigated. The results indicate that MSCs overexpressing HOTAIR produce EVs with increased HOTAIR content that promote angiogenesis and wound healing in diabetic (db/db) mice.